Soroprevalência de infecções víricas em cães de Santa Maria, RS; seleção e caracterização de linhagens celulares resistentes ao vírus da diarréia viral bovina - Dezengrini, Renata (2006)
The present study reports a serologic survey of the main viral infections of dogs in Santa Maria, RS, Brazil, and the production of cell lines of canine, swine and leporine origin resistant to bovine viral diarrhea virus (BVDV). Canine distemper virus (CDV), parvovirus (CPV), adenovirus (CAV) and coronavirus (CCoV) infections have been associated with significant morbidity and mortality among dogs worldwide. The aim of this study was to determine the prevalence of antibodies against these viruses in the canine population of Santa Maria. To this purpose, 817 blood samples were collected from non-vaccinated dogs of 14 neighborhoods and tested by virus neutralization (CDV, CAV and CCoV) and by hemagglutining inhibition (CPV). Specific antibodies to CDV were detected in 27.3% (223/817) of the samples, to CPV in 68.7% (561/817), to CAV in 43% (353/817) and to CCoV in 50.4% (412/817) of the dogs. These results indicate that CDV, CPV, CAV and CCoV infections are spread among dogs in Santa Maria. However, a significant part of the population is seronegative and therefore unprotected against these viruses. This indicates a need for extending the vaccination programs against these viruses. During the standardization of serologic tests and expansion of cell cultures for virus amplification, the canine MDCK cell line was found to be contaminated with BVDV, the main viral contaminant of cultured cells. The inadverted contamination of cultured cells with BVDV may represent a serious problem for diagnostic virology, research and production of biologicals. The second part of this dissertation reports the production and characterization of three cell lines resistant BVDV, obtained out of each parental cell line (canine MDCK, porcine PK-15 and leporine RK-13) that were contaminated with BVDV. Initially, the cells were submitted to four rounds of infection with a highly cytolytic BVDV strain. The cells surviving infection were then cloned out, expanded and assayed for their susceptibility to BVDV. The resistance to BVDV was investigated by search for viral proteins by immunofluorescence and by cocultivation with susceptible cells following inoculation of BVDV at high titers. All three cell lines were resistant to three standard BVDV strains (Singer, NADL e Oregon) and 10 field isolates. Inoculation of these cells with BVDV at a multiplicity of infection of 10 TCID50/cell resulted in frequencies of infection of <10-5 for MDCK-R and PK-15R cells and of 3,3x10-4 for RK- 13R. Compared to the parental ones, the resistant cells were >10.000 (MDCK-R), >20.000 (PK-15R) and 600 (RK-13R) times less susceptible to BVDV. The inoculation of virus in the resistant cells in the presence of polyethylene-glicol (PEG) resulted in an increase in susceptibility in the order of >437 (MDCK-R), >346 (PK-15R) and 87 (RK-13R) times. These results indicate that the resistance of these cell lines is probably due to a block in viral entry which can be overcome by addition of PEG. On the other hand, each resistant cell line retained the susceptibility to other three viruses of interest which replicate in the parental cells. Thus, these cells may be useful for virology diagnostic, virus propagation and for vaccine production, without the risk of being inadvertedly contaminated with BVDV.